Life, death, and ethics: medical and dental students’ attitudes on assisted dying in Austria - Carmen Trost; Julia S. Grundnig; Marlen A. Roehe; Anahit Anvari-Pirsch; Anita Holzinger (BMC Health Services Research)
Abstract Background The Sterbeverfügungsgesetz (StVfG) Austria’s law on assisted dying, came into force on January 1, 2022. Since then, only limited research has examined the attitudes of medical and dental students in Austria toward assisted dying. To address this gap, a survey was conducted among medical and dental students at the Medical University of Vienna, as they represent potential future opinion leaders. Understanding their perspectives is essential for the effective implementation and future development of assisted dying within the public healthcare system. Methods An online survey was conducted between May and June 2023. The questionnaire included two open-ended questions designed to capture medical and dental students’ personal reasons for and against assisted dying. Responses were analyzed using Mayring’s qualitative content analysis and categorized into micro (individual), meso (institutional) and macro (societal) levels. Results Of 5526 eligible students, 337 responded (response rate 6.1%). Key arguments in favor of assisted dying included subjective considerations like autonomy, relief of suffering, and dying with dignity. Main counterarguments highlighted societal concerns such as potential misuse (e.g., inheritance fraud or murder), legal uncertainties, and financial reasons. Less focus was given to immediate social impacts like the psychological burden on medical staff. Conclusions The diverse perspectives reflect a spectrum of ethical and practical considerations. Incorporating assisted dying, along with its ethical and legal issues, into the medical curriculum is essential for fostering a comprehensive understanding. Moreover, ongoing debates indicate the need for a thorough review of the legal framework to address loopholes and consider potential revisions.